An antibody of TNF-alpha did not prevent thioacetamide-induced hepatotoxicity in rats - Demirel, Ulvi; Harputluoglu, Murat M. M.; Seckin, Yuksel; Ciralik, Harun; Temel, Ismail; Ozyalin, Fatma; Aladag, Hulya (Sage Publications Ltd, 2011)
Tumor necrosis factor (TNF)-alpha antibodies have been shown to reduce liver damage in different models. We investigated the effects of infliximab (a TNF-alpha antibody) on liver damage in thioacetamide (TAA)-induced hepatotoxicity in rats. Group 1 (n = 8) was the control group. In group 2 (n = 8), the TAA group, the rats received 300 mg/kg intraperitoneal (ip) TAA daily for 2 days. In group 3 (n = 8), the TAA + Infliximab (INF) group, infliximab (5 mg/kg ip daily) was administered 48 hours before the first dose of TAA daily for 2 days and was maintained for 4 consecutive days. In group 4 (n = 8), the INF group, the rats received only ip infliximab (5 mg/kg) daily. Livers were excised for histopathological and biochemical tests (thiobarbituric-acid-reactive substances [TBARS], and myeloperoxidase [MPO]). Serum ammonia, aspartate transaminase (AST), alanine transaminase (ALT), TNF-alpha, liver TBARS and MPO levels, and liver necrosis and inflammation scores in the TAA group were significantly higher than in the control and INF groups (all p < 0.01). All parameters except AST were not significantly different between TAA and TAA + INF. In conclusion, our results suggest that oxidative stress plays an important role in TAA-induced hepatotoxicity, and infliximab does not improve oxidative liver damage.
Keywords: infliximab; tumor necrosis factor-alpha; thioacetamide; oxidative stress; liver